2017
DOI: 10.1002/jib.435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dimethyl sulphoxide reductase from brewing yeast

Abstract: Dimethyl sulphoxide (DMSO) reductase is present in all brewing yeast strains tested, but is more readily detectable using activity stains on polyacrylamide gels than through direct spectrophotometric assay of crude extracts. The enzyme is detectable at higher activities in yeast cultivated at lower temperatures and this is because of increased expression of the primary gene that codes for the enzyme in yeast, MXR1. DMSO somewhat increases enzyme expression, notably in lager yeast by up to 70%, whereas methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…This led to our work demonstrating that yeast does indeed convert DMSO (which we showed to be present in malt, especially after curing) into DMS . I demonstrated that the enzyme involved was methionine sulfoxide reductase ( , see also ). This is an enzyme present in many eukaryotes which serves the function of recycling methionine sulfoxide to methionine and thereby restoring its functionality.…”
Section: Dimethyl Sulphide (Dms)supporting
confidence: 87%
“…This led to our work demonstrating that yeast does indeed convert DMSO (which we showed to be present in malt, especially after curing) into DMS . I demonstrated that the enzyme involved was methionine sulfoxide reductase ( , see also ). This is an enzyme present in many eukaryotes which serves the function of recycling methionine sulfoxide to methionine and thereby restoring its functionality.…”
Section: Dimethyl Sulphide (Dms)supporting
confidence: 87%